An Analysis of the Tendency Towards the Religious and Spiritual Studies in Management in the National and International Areas - Alinaghi Amiri; Masoud Bananfi (پژوهش‌های مدیریت عمومی, 2024)
AbstractFor a long time, conventional humanities did not include religious and spiritual concepts in its domain. During the recent decades, the number of management research conducted in the field of religion, sprituality and ethics in the world has increased significantly, which indicates a change in some theoretical orientations of this field. In Iran, parallel to the international environment, the production of management works centered on religion and ethics has increased. The purpose of this article is to examine the religious and spiritual researches produced in the international domain in the field of management and its relationship with the research conducted in Iran. Is there a conceivable relationship between these two streams (conventional knowledge flow and native knowledge flow)? Why conventional management has given scientific and scientific status to religious and spiritual issues? This research has used qualitative survey methodology to answer its questions. The statistical population includes all research related to this issue. For sampling, the diversity in selection was observed. To analyze the data, the reasoning method and enumeration of all possible logical possibilities is used. For this purpose, by proposing hypotheses, it raises the possible possibilities of tendency toward religious management and the publication of works in the West, and by proposing arguments, it examines the relationship between two conventional currents and the indigenous current. The results show that the possibility of paradigm change, the need to solve society's problems, pluralism for survival, political possibility (religious confrontation), the awakening of nature, the use of tools and the acquisition of authority are among the reasons for the tendency to increase religious and spiritual works in the West. This increase in Iran is due to solving issues and problems, explaining Islamic management, political reason, fad and imitation. As well, it seems that the tendency towards spiritual works in the West is a tool to deal with the original religious trend and a return to the individual and secular religion of the Renaissance period, which has been manifested in a new form. Introduction For decades, the theory of organization and management has been influenced by a powerful force (Abedi Jafari et al., 2017). A force that was previously, for some reason, less popular with the scientific community and its capacity was neglected. But, today, the use of this capacity both in the theoretical dimension (Nafis, 2016; McClure, 2016; Lounsbury et al., 2014; Chan-Serafin et al., 2013;) both in the practical and professional dimension and in the journalistic literature and Popular (Sutton, 2013) has been in the spotlight. A capacity that does not seem to have been actively and consciously confronted in the Iranian research literature. This force or capacity is nothing but religious and spiritual issues in management.After many years of overcoming the idea of ​​separating knowledge from value and the necessity of science being free from human values ​​(Stufflebeam & Coryn, 2014: 22-65), the world's academic circles are witnessing the return of conventional management to ideas and concepts that are religious in nature. The upward trend of this movement has been evident in the last three decades. On the other hand, after the victory of the Islamic Revolution, along with the introduction of Western ideas and concepts of management and its reflection in the university community, a number of researches have focused on ethical, spiritual and Islamic issues in the field of management. The increase in the number of articles, publications, dissertations and content analysis of the views of experts in this field is evidence of this claim (Abedi Jafari, Banafi, Dastyari , 2020).Why has management, in its modern sense, which has been largely anti-values ​​and anti-spiritual, returned to this concept over time, especially after the 1970s? (Gundolf & Filser, 2013) Similarly, why has the tendency to produce works of religious-Islamic, moral and spiritual management increased in Iran? Perhaps until two or three decades ago, colleges and some experts in this field in the country, stood against the course of Islamic management issues or showed an inertia against its movement and prevented its reflection in dissertations and articles. In a way, such discussions were considered contrary to the general flow of management science or knowledge. Gradually, however, this resistance diminished and the number of published works increased. This has gone so far that in addition to new conferences and curricula, even in doctoral programs, treatises on moral, spiritual and Islamic topics are approved and compiled as new interdisciplinary approaches. Really, what is the reason for this change?In general, the reason for the increase in the growth of religious and spiritual works in management in the West can have several reasons. MethodologyThe overall design of the research is based on the qualitative survey methodology, and based on that, the objectives, sampling and data collection have been conducted. This type of survey does not count the number of community members; Rather, it seeks to identify meaningful diversity in society (not distribution) (Jansen, 2010). According to the guidelines of this method, the domain of research can be any subject, dimension or phenomenon. Sampling continues in a diverse manner and based on diversity coverage until saturation is reached. Data collection can also be conducted at any level and in any way (Jansen, 2010). According to this methodology, a variety of publications, articles, books, reports, and other related documents (in domestic and foreign electronic scientific databases and general internet search engines) were the scope of this research and formed the statistical population of this research. In the field of each of the works, the purposeful sampling and referring to the evidence has continued until covering the diversity and reaching theoretical saturation. More than one hundred publications, articles, books, reports, and other related documents have been reviewed. In the data analysis section, the reasoning method and enumeration of all possible logical possibilities have been used, and in some cases, the works have been analyzed for their content and their implications have been used.Conclusion and Results This research has focused on the force and phenomenon that in recent decades, has influenced the flow of conventional research in the field of management in the world and also in Iran. This phenomenon is the same as religion, morality and spirituality. Reflecting on this process, the authors have considered several possibilities for tending to this issue and producing massive research in this field in the West. These possibilities are: the possibility of paradigm, the need to solve society's problems, pluralism for survival, the possibility of political (religious confrontation), the possibility of awakening nature, the possibility of instrumental use, the possibility of expanding the range of concepts (gaining authority).Implications Based on what has been said, scholars in this field should be sensitive to the current of published research on Islamic, religious, spiritual and moral management in the country and be aware of the orientation towards the production of such works, especially regarding the possibility of fashionism; If so, the flow of knowledge within the country will not seek to solve the problem; Rather, it has used the wave created in the dominant discourse literature to justify his face. With the reduction of this possible mode, the heat of the flow of religious, spiritual and moral research in the country will also be reduced. The challenges in the social and administrative system and the body of business should be the basis for attention to religious and spiritual research, not the possible fashionism prevailing in the field of science. The needs and problems of society such as injustice, suicide, consumerism, economic culture, divorce, etc. should be the stimulus to raise religious and spiritual issues in management, not the desire for imitation and conformity. The flow and volume of possibilities for the production of religious and spiritual works in the country, whatever the extent, it should be acknowledged that so far, less research has been considered in terms of growth and its importance at the international level, and it seems that, He did not pay attention to the importance of this issue for solving problems and was more of a function than a driver. The next decade of religious and Islamic management in the country should be focused on deep understanding of the main issues of Islamic society, the system of government and individual and social issues to follow the wave of production of works that sometimes take on the color of conventional topics and puzzles of a map It does not meet the real needs of the natives.